APPLICATION OF STEEL FIBRES IN ALKALI-ACTIVATED MORTARS - Götz Hüsken; Lars-Christian Wagner; Gregor J. G. Gluth; Stephan Pirskawetz; Hans-Carsten Kühne (Acta Polytechnica CTU Proceedings, 2020)
Alkali-activated materials are ideal for the repair of concrete structures in harsh environmental conditions due to their high durability in chemically aggressive environments. However, slag-based mortars, in particular, are prone to shrinkage and associated cracks. In this respect, the application of steel fibres is one solution to reduce the formation of shrinkage induced cracks and to improve post cracking behaviour of these mortars. This study investigated the influence of two different types of steel fibres on the tensile properties of two alkali-activated mortars. Direct tensile tests and single fibre pull-outs were performed to analyse the determining failure modes both on macro and micro scale. Mechanical testing was accompanied by non-destructive testing methods such as digital image correlation and acoustic emission for a detailed analysis of the fracture process.